Especially the Textbooks Created by Sadriddin Ayniy (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is devoted to the research of Sadriddin Aini's practical efforts in the field of education in the beginning of the 20th century, in particular, his significant work in opening new style schools and creating textbooks. In particular, the textbooks "Zaruriyoti diniya" and "Tahsib-us Sibyon" are mentioned. The article focuses on the important aspects of Ayni's unique style and opinions.